Prevalence of Head Pediculosis Among Refugees In Sulaimani Governorate/ Kurdistan- Iraq - Ali, Fatimah Mohammed; Hama, Abdullah Ahmed (Iraqi Journal of Science, 2018)
The head louse (Pediculus humanus capits) is one of the common obligate ectoparasites blood-sucking, wingless, belonging to the order Phthiraptera, sub-order Anoplura which are specific parasites of a human being with the medical importance worldwide. This study carried out to estimate the prevalence of head pediculosis and its associated factors among refugees in Sulaimani province. Total of 11798 peoples participated in this study including 5056 male and 6742 female from five refuges campus in Sulaimani province, the direct inspection visually followed to detect head lice infestation (pediculosis). The overall prevalence in the current study was 1.12%, the infestation was significantly higher among female (1.78 %) than the male (0.24 %). The age significantly had an effect on the pediculosis; the higher rate of pediculosis was among children (1-5 years) than the other age groups although Pediculosis was significantly higher among low-level educational peoples (preparatory and primary). The family size, hair washing duration, length of hair and type of hair have the direct effect of the head louse infestation, while the significant association between scalp disease (Dandruff) and infestation rate of head lice was not observed. From this study, we conclude the prevalence of head lice has directly related to age, personal hygiene, and hair type, and the refugee's camps in Sulaimani province (Kurdistan-Iraq) need more health care and health awareness.